Tetrakis(4‐amino‐1, 2, 4‐triazole)platinum(II) Salts: Syntheses, Crystal Structures, and Properties1. Issue 5 (12th February 2014) - Carpenter, Julia A.; Dshemuchadse, Julia; Busato, Stephan; Bräunlich, Irene; Pöthig, Alexander; Caseri, Walter
Abstract Transparent crystals comprising the nitrogen‐rich coordination unit [Pt(NH2trz)4]2+ were synthesized with counterions of various sizes but of the same charge (–1), yielding the compounds [Pt(NH2trz)4]Cl2·2H2O, [Pt(NH2trz)4](NO3)2 and [Pt(NH2trz)4](CF3SO3)2, with NH2trz designating 4‐amino‐1, 2, 4‐triazole. Single‐crystal X‐ray diffraction analysis showed that NH2trz coordinates with only the nitrogen atom in 1‐position in all compounds. The [Pt(NH2trz)4]2+ units are stacked such that the platinum atoms form linear arrays with Pt–Pt spacings mostly uncorrelated to anion size. The compound with the smallest anion (Cl–) has the smallest Pt–Pt spacing (4.72 Å) and shows a quasi‐one‐dimensional structure. Thermal decomposition of the compounds was observed around 200 °C. Electrical conductivity of [Pt(NH2trz)4]Cl2 and [Pt(NH2trz)4](SO3CF3)2 was investigated and found to be humidity‐dependent. Finally, [Pt(NH2trz)4]2+ ions obtained by dissolution of the chloride salt are shown to be useful for the synthesis of new compounds such as the Magnus' salt derivative [Pt(NH2trz)4][PtCl4].